Effect of yeast culture supplementation in sows during late gestation and lactation on growth performance, antioxidant properties, and intestinal microorganisms of offspring weaned piglets - Liu, Yalei; Jia, Xinlin; Chang, Junlei; Jiang, Xuemei; Che, Lianqiang; Lin, Yan; Zhuo, Yong; Feng, Bin; Fang, Zhengfeng; Li, Jian; Hua, Lun; Wang, Jianping; et al. (Frontiers in Microbiology, 2023)
The effects of maternal addition of yeast cultures on offspring gut development and intestinal microorganisms are not yet known, so the aim of this study was to investigate the effects of maternal addition of yeast cultures to the diet of sows during late gestation and lactation on growth performance, antioxidant properties and intestinal microorganisms of offspring weaned piglets. 40 Landrace × Yorkshire sows (3-7 of parity) with similar backfat were randomly divided into two treatment groups: control diet (CON) and control diet + 2.0 g/kg yeast culture (XPC), and the trial started on day 90 of gestation and ended on day 21 of lactation. The results showed that maternal addition of yeast culture significantly increased weaned piglet weight and mean daily gain (P < 0.05), with a tendency to increase litter weight gain (P = 0.083) and liver weight (P = 0.076) compared to the control group. The content of thymus malondialdehyde (MDA) was significantly higher (P < 0.05) and the content of colon total antioxidant capacity (T-AOC) was significantly lower (P < 0.05) in the offspring weaned piglets of the XPC group compared to the control group. The expression of thymus SOD1 and SOD2, spleen SOD1, jejunum SOD2, and colon GPX1, SOD1, and SOD2 were significantly downregulated in the XPC group of offspring weaned piglets compared with the control group (P < 0.05). The intestinal morphology and the content of short-chain fatty acids in colonic chyme did not differ between the two groups (P > 0.05). Compared with the control group, the XPC group significantly increased the relative abundance of colonic chyme Bacteroidetes (P < 0.05), tended to decrease the relative abundance of Lactobacillus (P = 0.078), and tended to increase the relative abundance of Alloprevotella (P = 0.055). The XPC group significantly upregulated Blautia and Fournierella (P < 0.05) and significantly downregulated Candidatus_Competibacter, Nitrospira, Dechloromonas, Haliangium, and Oscillospira (P < 0.05). In conclusion, maternal addition of yeast cultures improved the growth performance of offspring weaned piglets and changed the intestinal microbial community, but did not improve their antioxidant performance.